2006
DOI: 10.1111/j.1365-313x.2006.02889.x
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis heat shock transcription factor A2 as a key regulator in response to several types of environmental stress

Abstract: SummaryWe isolated 76 high-light and heat-shock (HL þ HS) stress-inducible genes, including a putative heat-shock transcription factor (HsfA2), by suppression-subtractive hybridization from Arabidopsis. The transcript level of HsfA2 was significantly increased under the several stress conditions or by the H 2 O 2 treatment. Furthermore, the induction of HsfA2 expression was highest among those of other class A HSFs in response to HL þ HS stress conditions. The promoter assay revealed that HsfA2 is induced main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
450
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 486 publications
(488 citation statements)
references
References 53 publications
(51 reference statements)
21
450
1
3
Order By: Relevance
“…3A). Interestingly, several putative HsfA2 targets (Nishizawa et al, 2006;Schramm et al, 2006) are also induced by anoxia (Fig. 3B).…”
Section: Heat Pretreatment Dampens the Anaerobic Responsementioning
confidence: 99%
See 1 more Smart Citation
“…3A). Interestingly, several putative HsfA2 targets (Nishizawa et al, 2006;Schramm et al, 2006) are also induced by anoxia (Fig. 3B).…”
Section: Heat Pretreatment Dampens the Anaerobic Responsementioning
confidence: 99%
“…Interestingly, it seems that in Arabidopsis, different from tomato (Solanum lycopersicum; Mishra et al, 2002), there is not a unique master regulator for the Hsf-mediated heat shock response. Different Hsfs have been identified as potential crucial element for Arabidopsis response not only to heat stress (Busch et al, 2005;Schramm et al, 2006Schramm et al, , 2008Charng et al, 2007) but also to oxidative stress (Li et al, 2005;Nishizawa et al, 2008), hydrogen peroxide (H 2 O 2 ), high light (Nishizawa et al, 2006), and salt stress as well (Ogawa et al, 2007).…”
mentioning
confidence: 99%
“…We previously isolated a gene encoding a NAC transcription factor named ANAC078 according to the nomenclature established for the Arabidopsis NAC family 11,12 though it has also been designated NTL11. 13 Furthermore, we reported that the transcript levels of 166 genes in ANAC078-overexpressing Arabidopsis plants (Ox-ANAC078) are increased compared with those in the wild-type plants under HL.…”
mentioning
confidence: 99%
“…In addition, targets of MAPK proteins are mainly TFs (Popescu et al, 2009), underlining the direct connection with the MAPK signal cascade. The expression of many TF genes, including members of the HSF, WRKY, C 2 H 2 zinc-finger, bZIP, MYB, and AP2/ERF families, has been shown to be H 2 O 2 induced (Miao et al, 2004;Nishizawa et al, 2006;Davletova et al, 2005;Sun et al, 2010;Yun et al, 2010). Several zinc-finger proteins (ZFPs) contribute to salt tolerance by modulating oxidative stress responses.…”
Section: Introductionmentioning
confidence: 99%